The Effect of Zinc Oxide Scallop-Shell Powder and Complications After Coronary Angiography - Marjan Rahmani; Arsalan Salari; Mohammad-Taghi Moghadamnia; Saeed Omidi; Mehdi Shirzad-Siboni; Majid Pourshaikhian (Journal of Holistic Nursing and Midwifery)
Introduction: Coronary angiography is often associated with complications such as hemorrhage and hematoma that should be considered and be minimized. Objective: This study aimed to determine the effect of Zinc oxide scallop-shell powder as a topical hemostatic agent (composed mainly of calcium) on complications after coronary angiography. These complications include hemostasis time, low back pain, hemorrhage, hematoma, the necessity of sandbags, and patient ambulation. Materials and Methods: The current research was a blind, parallel, randomized clinical trial done on 150 patients under coronary angiography. They were randomly divided into three equal groups of A (control), B (case 1), and C (case 2). In group A, hemostasis was done with manual compression, use of ChitoHem powder, putting sandbag for 4-6 h in a supine position, and getting out of bed after 24 h. In group B, instead of ChitoHem powder, we used Zinc oxide scallop-shell powder. In group C, hemostasis was done with manual compression, Zinc oxide scallop-shell powder, putting sandbag for 1 h in a supine position, and getting out of bed after 2 h. The duration of hemostasis, bleeding, and hematoma after hemostasis and the severity of low back pain were investigated at 8 point intervals during 24 h. Data analysis was done using descriptive statistics indicators and Kolmogorov-Smirnov, ANOVA, Chi Square, Fisher exact test and Kruskal-Wallis tests. Results: The mean ±SD ages of groups of A, B, and C were 60.08 ±11.32, 60.22 ±10.30, and 61.69 (10.61), respectively, which was not statistically different. Furthermore, there was no significant difference between these three groups regarding their demographic information. There were statistically significant differences between groups about the amount of low back pain at the second, third, and fourth hours after angiography (P= 0.001). There was a significant difference in the amount of bleeding between the three groups (P=0.017). The difference in time of hemostasis in the three groups was not statistically significant. Conclusion: The Zinc oxide scallop-shell powder reduces catheter site bleeding after coronary angiography and bed rest time and ultimately the severity of low back pain. Performing a similar study is recommended.